The deadly secret of dorothy w. - Blake, Jon; Paul, Korky (Hodder Children's London, 2003)
When Jasmin wins a place at the Dorothy Wordsearch School for Gifted Young Writers, things look fishy. As Jasmin unravels the deadly secret she finds herself writing for her life. Now, only the most brilliant story will help her survive! Suggested level: primary